1992
DOI: 10.1152/ajpcell.1992.263.5.c1040
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular nucleotides elevate [Ca2+]i in rat osteoblastic cells by interaction with two receptor subtypes

Abstract: Extracellular nucleotides, through interaction with specific cell-surface receptors, mediate a variety of biological responses, including elevation of cytosolic free Ca2+ concentration ([Ca2+]i) in a number of cell types. The effects of nucleotides on [Ca2+]i in the rat osteoblastic cell line UMR-106 were studied by fluorescence spectrophotometry of indo-1-loaded cells. In response to ATP (100 microM), [Ca2+]i rose to peaks 228 +/- 16 nM (n = 59) above baseline (85 +/- 3 nM) before returning to near basal leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 16 publications
7
57
0
Order By: Relevance
“…Although the extracellular concentrations of nucleoside triphosphates such as ATP are generally low in comparison with their intracellular concentrations, many cell types can release ATP in a controlled fashion through exocytosis or via cell membrane transport, generating extracellular concentrations in excess of 1 mM [26][27][28][29]. Notably, extracellular nucleoside triphosphates at micromolar concentrations are ligands for cell surface P2 purinergic receptors that have been implicated in a variety of biological processes including neuronal [30,31] and smooth muscle activity [32], platelet aggregation [25] and bone cell regulation [33][34][35][36][37]. Although the extracellular ATP concentration near active osteoblasts in i o is not known, it is conceivable that sufficiently high levels of extracellular ATP can be produced to provide substrate for ectokinases that have K m values that range from 10 mM down to 0.04 mM [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although the extracellular concentrations of nucleoside triphosphates such as ATP are generally low in comparison with their intracellular concentrations, many cell types can release ATP in a controlled fashion through exocytosis or via cell membrane transport, generating extracellular concentrations in excess of 1 mM [26][27][28][29]. Notably, extracellular nucleoside triphosphates at micromolar concentrations are ligands for cell surface P2 purinergic receptors that have been implicated in a variety of biological processes including neuronal [30,31] and smooth muscle activity [32], platelet aggregation [25] and bone cell regulation [33][34][35][36][37]. Although the extracellular ATP concentration near active osteoblasts in i o is not known, it is conceivable that sufficiently high levels of extracellular ATP can be produced to provide substrate for ectokinases that have K m values that range from 10 mM down to 0.04 mM [32].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent pharmacological studies revealed that extracellular nucleotides interacted with at least two P2 receptors (P2Y1 and P2Y2) on rat osteoblastlike cells (Reimer et al, 1992;Yu et al, 1993b). The first molecular evidence for P2Y receptor expression was shown in 1995 by Bowler et al, who used RT-PCR and in situ hybridisation to demonstrate P2Y2 receptor expression in human osteoblasts (Bowler et al, 1995).…”
Section: The Role Of Purinergic Signalling In Osteoblast Biologymentioning
confidence: 99%
“…We and others have shown that ATP and other nucleotides are released in response to fluid shear stress in vitro and activate purinergic (P2) receptors on the membrane of the osteoblasts (13,20,29,38). Although many subtypes of P2 receptors are present in osteoblasts (4), knockout of the purinergic receptor P2X 7 R, a ligand-gated ion channel, resulted in an osteopenic phenotype (22), suggesting that this receptor is important in skeletal maintenance.…”
mentioning
confidence: 99%